Localization of single-copy sequences on chicken synaptonemal complex spreads using fluorescence in situ hybridization (FISH) - Pigozzi, Maria Ines (2007)
Synaptonemal complex (SC) spreads from bird oocytes and spermatocytes show the complete chromosome complement and can be observed at the light microscope using immunostaining of the proteins that compose the lateral elements. To investigate the use of avian SC spreads as substrates for fluorescent in situ hybridization (FISH) in combination with immunostaining, we applied two single-copy sequences to chicken oocyte spreads. Signals for both target sequences were consistently observed on the short arm of bivalent 1 in a large number of nuclei. Based on previous data about the size of chromosome 1 and from measurements on probed SC spreads, an estimate of the physical distance in Mb between each sequence and the telomere was calculated. The crossover frequencies along SC 1 obtained by immunolocalization of MLH1 foci during pachytene were used to calculate the distances in cM to the target sequences and to compare this cytogenetic SC map with the consensus linkage map for GGA1. The combination of SC-FISH and immunostaining could be generally applied to obtain high-resolution mapping of single-copy sequences in birds and, coupled with MLH1 crossover maps, it could be a reliable approach to obtain genetic distances between markers to test the genetic linkage maps generated from molecular markers.